The Trend of Urinary N Terminal Probrain Natriuretic Peptide in Extremely Low Birth Weight Infants during the Neonatal Period - Khan, Safdar S.; Bada, Henrietta S.; Torres, Maritza; Almodovar, Melvin; Hanna, Mina (American Journal of Perinatology, 2021)
Objective N-terminal probrain natriuretic peptide (NT-proBNP) is a biomarker of interest in many cardiopulmonary diseases in extremely low birth weight (ELBW) Infants. However, there is a gap in knowledge about the trend of ELBW infant's urinary NT-proBNP during the neonatal period.Aim To determine the trend of urinary NT-proBNP during the first 4 weeks of life of an ELBW infant.Study Design We analyzed prospectively enrolled 87 ELBW infants. Urinary NT-proBNP to creatinine ratios were measured on days 1 to 7, 14, and 28 of life. We plotted each study point's means to determine the trend of urinary NT-proBNP over the entire neonatal period. Data were analyzed using the Friedman analysis of variance for comparative analysis of study points.Results Urinary NT-proBNP/creatinine ratios were significantly elevated on days 1 to 7 (mean 2,452, ± 1,518) than day 14 (mean 747, ± 176), and day 28 (mean 149, ± 54), p = 0.001. Overall, urinary NT-proBNP levels were highest during days 1 to 3 (mean 3,232, ± 1,255) and lowest on day 28 (mean 149, ± 54).Conclusion Urinary NT-proBNP levels are higher during the first week in ELBW infants with a downward trend during the neonatal period, the lowest values at 4 weeks postnatal age. More studies are required to determine the clinical utility of this trend during and beyond the neonatal period.Key Points
Keywords: NT-proBNP; trend; premature; infants